Risque des phtalates contenus dans les dispositifs médicaux sur la santé des patients - JOUIDA , Abdelkarim; EL MARNISSI, Safaa; RHANIM , Halima; ARBAI , Soumaya; AARIF , El Hassan; AIT EL CADI, Mina (Jour Med Resh and Health Sci, 2023)
Introduction: Medical devices are devices used in the majority of therapies in hospitals. Up to 30% of medical devices are made of plasticized PVC, this plasticization is ensured by phthalates which are the most used plasticizers, but they are also dangerous molecules for human health. Method: Therefore, the objective of this study was to evaluate the risk related to the use in patients of MD based on PVC plasticized by phthalates. To achieve this objective, the MD with phthalates in CHUIS were identified and their risk was evaluated using the equation: Risk = Hazard x Exposure. Results and discussion: In this study we found 15.94% of the MD managed by the CHUIS pharmacy based on plasticized PVC, 47.5% of them were plasticized with phthalates. These MD were classified according to their risk relative to phthalates, 57.9% were of low risk, they are MD used for urine and blood drainage, oxygenation and perfusion. About 10.52% of the MD were medium risk, these MD are in contact with blood and digestive tract. In addition, 26.31% of the high-risk MD, which are all characterized by their contact with blood, which increases their dangerousness. And 5.26% of the very high-risk MD characterized by their prolonged contact with the organism and their contact with cytotoxic drugs.